JURIDICAL ANALYSIS OF SHARIA-BASED ORAL HEALTH SERVICES IN HOSPITALS - Sukini, Sukini; Santoso, Moh Imam; Aditya, Alif Krisna (Universitas 17 Agustus 1945 Semarang, 2024)
This article aims to provide an analysis of the intersection of Islamic Sharia principles, legal frameworks, and professional standards in the context of oral health care provided in hospitals. This research will offer a comprehensive review of how these elements interact to shape the ethical and legal landscape of dental and oral health services. The study employs a normative juridical research approach with a legislative perspective, utilizing library research data that is analyzed qualitatively in a descriptive manner. The analysis reveals that, from an Islamic perspective, health is considered a divine gift that each individual must be accountable for, and it is crucial for patient satisfaction in achieving optimal health outcomes. The role of stakeholders is vital to ensure the delivery of high-quality services, necessitating the implementation of robust health service standards that prioritize responsibility, safety, equity, and inclusivity. Furthermore, stakeholders need to further examine the significance of oral health in Islamic views, emphasizing its role in the digestive system and religious practices. This research delves into the development of Sharia-based health sectors, including hospitals, medical device manufacturers, and pharmaceutical companies, with a focus on patient-centered care and the integration of Islamic values. The roles of oral health professionals, such as dentists and dental therapists, are highlighted, with an emphasis on the importance of ethical and patient-centered practices. Overall, this study aims to contribute to a comprehensive understanding of how Sharia principles can enhance oral health services and optimize individual well-being